Belimumab-driven reductions in retinal microvascular density assessed by optical coherence tomography angiography: insights from systemic lupus erythematosus patients - Maitiyaer, Maierhaba; Zhang, Jingyu; Li, Peiyi; Jiang, Dingwen; Li, Huangdong; Lin, Zeying; Ye, Ziguan; Huo, Yongbao; Huang, Wenhui; Wang, Li; Liu, Zhiping; Yu, Shuilian (Frontiers in Immunology, 2025)
BackgroundSystemic lupus erythematosus (SLE) and lupus nephritis (LN) are associated with retinal microvascular changes that may reflect disease severity. This study aimed to evaluate differences in retinal vascular density (VD) between SLE patients with and without LN and assess the impact of rheumatological treatments on VD.MethodsA cross-sectional study was conducted with 54 SLE patients (21 with LN, 33 without LN). Retinal VD was measured using optical coherence tomography angiography (OCTA), focusing on superficial and deep capillary plexus VD (SCP-VD and DCP-VD). The impact of Belimumab and other treatments was analyzed. Linear regression assessed the effects of LN status and treatments on DCP parafoveal VD. Lymphocyte subsets and cytokines were compared before and after Belimumab treatment.ResultLN patients showed significantly reduced macular vascular density compared with non-LN patients. Belimumab treatment (≥8 times) and hydroxychloroquine use (>5 years) were independently associated with lower DCP-VD, particularly in parafoveal areas. Cumulative doses of HCQ and glucocorticoids negatively correlated with VD. Linear regression showed a significant negative association between Belimumab treatment and parafoveal DCP-VD. Notably, Belimumab treatment led to reductions in serum CD19+ B cells and IL-10 levels.ConclusionsLN patients demonstrated distinct retinal microvascular alterations. Long-term Belimumab and HCQ treatments were associated with decreased retinal VD. Regular retinal health monitoring was recommended to prevent microvascular complications in SLE patients undergoing prolonged treatment.